Development of an autophagy activator from Class III PI3K complexes, Tat-BECN1 peptide: Mechanisms and applications - He, Yanfei; Lu, Huaqing; Zhao, Yuting (Frontiers in Cell and Developmental Biology, 2022)
Impairment or dysregulation of autophagy has been implicated in many human pathologies ranging from neurodegenerative diseases, infectious diseases, cardiovascular diseases, metabolic diseases, to malignancies. Efforts have been made to explore the therapeutic potential of pharmacological autophagy activators, as beneficial health effects from caloric restriction or physical exercise are linked to autophagy activation. However, the lack of specificity remains the major challenge to the development and clinical use of autophagy activators. One candidate of specific autophagy activators is Tat-BECN1 peptide, derived from Beclin 1 subunit of Class III PI3K complexes. Here, we summarize the molecular mechanisms by which Tat-BECN1 peptide activates autophagy, the strategies for optimization and development, and the applications of Tat-BECN1 peptide in cellular and organismal models of physiology and pathology.